Ultrasound-Guided Synovial Biopsy: A Review - Saraiva, Fernando (Frontiers in Medicine, 2021)
Ultrasound-guided synovial biopsy is a safe, well-tolerated and effective mean to collect good quality synovial tissue for clinical and research purposes, in all types of joints. Although synovial biopsy cannot still be used to distinguish between two types of inflammatory rheumatic diseases, synovial tissue analysis has produced remarkable advances in the understanding of rheumatoid arthritis pathobiology and of other inflammatory rheumatic diseases. Being synovitis the hallmark of these diseases, accessing the core of the pathological process, synovial tissue, opens the door to gather information with potential diagnostic and prognostic utility.